Pengembangan Instrumen Tes Kemampuan Matematika untuk Mahasiswa Calon Guru Matematika - Annisa Dwi Kurniawati; Arkana Rezky Dhanurendra; Fiki Rahmita (Indonesian Mathematics Education Journal, 2024)
Research in mathematics education related to mathematical abilities, especially in prospective mathematics teacher students, is increasing. However, instruments related to mathematics ability tests for prospective mathematics teachers are still limited and rarely found. The three stages of the instrument development model, namely design, define, and develop, were carried out by researchers to produce mathematics ability test instruments aimed at prospective mathematics teacher students. Based on the development process and expert validation, the results showed that the mathematics ability test instruments developed by researchers met the valid criteria. So, the mathematics ability test instruments developed by researchers can be used and utilized for researchers in mathematics education who are interested in examining the mathematical abilities of prospective mathematics teacher students.